Interactive M-Learning Media Technology to Enhance the Learning Process of Basic Logic Gate Topics in Vocational School and Engineering Education - Aulia Akhrian Syahidi; Herman Tolle; Ahmad Afif Supianto; Tsukasa Hirashima; Kohei Arai (International Journal of Engineering Education, 2020)
The process of learning to use smartphones is now highly promoted. Almost everyone has a smartphone. The latest trend in learning is known as Mobile Learning (M-Learning). M-Learning can be used anywhere and anytime. Thus, we propose the use of the M-Learning application for computer system subjects in the basic logic gate topics so that students can be motivated to learn. We call this application BLG-LeMed. The focus of this research is on the process of using BLG-LeMed applications on classroom learning that is used directly by vocational high school students, then testing with alpha testing, User Acceptance Tests (UAT), usability evaluations, and knowing the effect of motivating students to use five dimensions of motivation and student learning outcomes. The development model used is Extreme Programming (XP). The design used in this study, by conducting trials in one class and observing students using the BLG-LeMed application as learning media, 38 students consisted of 26 men and 12 women involved in this study, with a duration of 135 minutes at one time of the meeting. We conclude that using the BLG-LeMed application based on M-Learning in the learning process of this basic logic gate, strongly supported by the testing team, can be accepted by users, has a usefulness as a interactive learning media, can have an effect in motivating students to learn, and provide results very satisfying learning.